2020
DOI: 10.1177/1756284820935033
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of lymph node metastasis and residual tumor in early gastric cancer patients after noncurative endoscopic resection: a systematic review and meta-analysis

Abstract: Background: It is challenging to identify the prevalence of lymph node metastasis (LNM) and residual tumor in patients with early gastric cancer (EGC) who underwent noncurative endoscopic resection (ER). This present meta-analysis was aimed to establish imperative potential predictive factors in order to select the optimal treatment method. Methods: A systematic literature search of PubMed, Embase, and Cochrane Library databases was performed through 1 February 2019 to identify relevant studies, which investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…In addition, this is crucial to determine whether a D1 LND is justified for early, T1-stage GC and whether a D2 LND is justified for more advanced gastric carcinomas. This review is consistent with previous literature studies reporting the metastases rate for the different T-stages [12,24,25]. These studies similarly show an overall low metastases rate in the early carcinomas and an overall high prevalence in the more advanced carcinomas.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, this is crucial to determine whether a D1 LND is justified for early, T1-stage GC and whether a D2 LND is justified for more advanced gastric carcinomas. This review is consistent with previous literature studies reporting the metastases rate for the different T-stages [12,24,25]. These studies similarly show an overall low metastases rate in the early carcinomas and an overall high prevalence in the more advanced carcinomas.…”
Section: Discussionsupporting
confidence: 92%
“…After non-curative resection, it is vital to confirm that LNM is absent, as this will determine whether or not additional surgery for post-ER patients is required. A recently published meta-analysis indicated that the risk of LNM was significantly increased in tumors that were > 30 mm in size, had an invasion depth of ≥ 500 μm, flat or elevated tumor macroscopic appearance, and were of the undifferentiated histopathological type, after resection, had positive vertical margins and indications of lymphovascular invasion (LVI) ( 94 ). Another meta-analysis reached similar conclusions and specifically pointed out that lymphatic invasion and vascular invasion individually, rather than LVI, should be assessed, because vascular invasion did not show a significant statistical difference ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have addressed factors to stratify the risk of LNM or residual tumour in patients who have had non-curative ESD. In regard to LNM, lymphovascular invasion (LVI) and depth of submucosal invasion histologically are reported to be the most consistent predictors[ 135 , 136 ]. Goto et al [ 134 ] reported that the presence of depth of invasion > SM1 or LVI was 100% sensitive and 86% specific for the presence of LNM[ 135 ].…”
Section: Endoscopic Treatment Of Gastric Neoplasiamentioning
confidence: 99%